Peptide‐Functionalized Fluorescent Particles for In Situ Detection of Nitric Oxide via Peroxynitrite‐Mediated Nitration. Issue 16 (17th May 2017) - Chang, Jason Y. H.; Chow, Lesley W.; Dismuke, W. Michael; Ethier, C. Ross; Stevens, Molly M.; Stamer, W. Daniel; Overby, Darryl R.
Abstract : Nitric oxide (NO) is a free radical signaling molecule that plays a crucial role in modulating physiological homeostasis across multiple biological systems. NO dysregulation is linked to the pathogenesis of multiple diseases; therefore, its quantification is important for understanding pathophysiological processes. The detection of NO is challenging, typically limited by its reactive nature and short half‐life. Additionally, the presence of interfering analytes and accessibility to biological fluids in the native tissues make the measurement technically challenging and often unreliable. Here, a bio‐inspired peptide‐based NO sensor is developed, which detects NO‐derived oxidants, predominately peroxynitrite‐mediated nitration of tyrosine residues. It is demonstrated that these peptide‐based NO sensors can detect peroxynitrite‐mediated nitration in response to physiological shear stress by endothelial cells in vitro. Using the peptide‐conjugated fluorescent particle immunoassay, peroxynitrite‐mediated nitration activity with a detection limit of ≈100 × 10 −9 m is detected. This study envisions that the NO detection platform can be applied to a multitude of applications including monitoring of NO activity in healthy and diseased tissues, localized detection of NO production of specific cells, and cell‐based/therapeutic screening of peroxynitrite levels to monitor pronitroxidative stress in biological samples. Abstract : Peptide‐conjugated fluorescent particles are developed as biosensors to detect nitric oxide (NO) based on 3‐nitrotyrosine labelling. The biosensors successfully detect NO release from endothelial cells under shear stress with a sensitivity exceeding that of standard assays. The biosensors provide an integrated measure of NO in the vicinity of the fluorescent particle, thereby allowing spatiotemporal localization of NO production within biological systems.